Withme Alarm App - Hana Fatiha, Hadzri (2023)
Ensuring the safety of individuals near us traditionally involves keeping them within sight or holding hands. However, incidents of people going missing still occur, particularly among parents and guardians of senior citizens with special needs. Additionally, in crowded areas like Bukit Bintang, Kuala Lumpur, Times Square, New York, or Myeong-dong, Seoul, remaining vigilant and navigating these bustling environments is crucial to prevent disorientation and loss. To address these challenges, the WithMe Alarm is introduced as a mobile application that employs geofencing technology. It allows registered monitors to track and monitor individuals, including children, senior citizens, or adults. When the monitored person goes outside radar, the app triggers an alarm to notify the monitor. The project development follows the Agile software process model, chosen for its adaptability to frequent changes in user and system requirements within a short duration. The testing process yields positive results, affirming the app's readiness for commercialization. The project successfully achieves its objectives within the defined scopes.